2021
DOI: 10.3390/mi12050512
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Silver Nanowires/Graphene Sandwich Composite for Stretchable Transparent Electrodes and Its Fracture Mechanism

Abstract: Polycrystalline graphene grown by chemical vapor deposition (CVD) is characterized by line defects and disruptions at the grain boundaries and nucleation sites. This adversely affects the stretchability and conductivity of graphene, which limits its applications in the field of flexible, stretchable, and transparent electrodes. We demonstrate a composite electrode comprised of a graphene/silver nanowires (AgNWs)/graphene sandwich structure on a polydimethylsiloxane substrate to overcome this limitation. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Cu with thickness of 3 nm exhibits a maximum current density of 12.64 mA/cm 2 [127]. Huang et al [128] reported a sandwich structure made of graphene and silver nanowire where silver nanowire is inserted between two layers of graphene. The stretchable properties of single layer graphene (SLG), double layer graphene (DLG) and sandwiched type structure was analyzed and it was observed that the resistance of the SLG was unmeasurable after 10 cycles, DLG have similar results after 40 cycles but the sand witched type gradually increased to 4 after 20 cycles.…”
Section: Transparent Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu with thickness of 3 nm exhibits a maximum current density of 12.64 mA/cm 2 [127]. Huang et al [128] reported a sandwich structure made of graphene and silver nanowire where silver nanowire is inserted between two layers of graphene. The stretchable properties of single layer graphene (SLG), double layer graphene (DLG) and sandwiched type structure was analyzed and it was observed that the resistance of the SLG was unmeasurable after 10 cycles, DLG have similar results after 40 cycles but the sand witched type gradually increased to 4 after 20 cycles.…”
Section: Transparent Electrodesmentioning
confidence: 99%
“…This structure effectively reduces the oxidation of the silver wire and withhold the initial resistance of the electrode. Furthermore, it possessed low sheet resistance, high light transmittance (greater than 90 %) and long-term stability when compared to that of SLG and DLG [128].…”
Section: Transparent Electrodesmentioning
confidence: 99%
“…Silver nanowire (AgNW), due to its high electrical conductivity, high flexibility, and high optical transparency, has been widely used as a promising conductive material for various applications such as photovoltaics, displays, touch panels, and smart windows . Additionally, AgNW-based composites such as AgNWs/PEDOT:PSS, AgNWs/graphene, AgNWs/graphene oxide (GO), AgNWs/carbon nanotubes (CNTs), and AgNWs/MXene have been widely used in flexible and stretchable electrodes and have been extended for wearable sensors and biomedical applications. Typically, Wang and co-workers used a capillary-force-induced method to fabricate stretchable AgNW/CNT composite electrodes with a low sheet resistance of 8.7 Ω·sq –1 , transmittance of 66.4%, and high stretchability of 490% . However, this work is mainly focused on electrical, optical, and mechanical performance, and there is still a lack of attention to electromechanical properties (such as strain-induced resistance change and hysteresis).…”
Section: Introductionmentioning
confidence: 99%
“…These components are suitable for wearable and patchable applications such as photovoltaic energy harvesters, human interactive sensors, and displays. , Flexible and transparent electrodes (FTEs) have been extensively explored, in particular for developing high-performance flexible displays based on self-light-emitting devices, such as quantum dot light-emitting diodes (QLEDs), organic light-emitting diodes (OLEDs), and polymer light-emitting diodes (PLEDs); , these devices can be readily combined with diverse solution processes for scalable, large-area applications. Based on a variety of solution-processable low-dimensional nanoscale conductors, such as carbon nanotubes, , reduced graphene oxides, and silver nanowires (AgNWs), a comparison of various solution-processable FTEs with sufficiently high conductivity and the conductivity of commercially available rigid indium tin oxide (ITO) has been demonstrated. The results are unsatisfactory owing to various material and technological limitations such as low conductivity (high surface resistance) and poor film quality caused by intrinsic structural defects and numerous physical junctions of nanoconductors required for percolated networks. ,, …”
mentioning
confidence: 99%